Real-world outcomes of the CROSS regimen in patients with resectable esophageal or gastro-esophageal junction adenocarcinoma: a nationwide cohort study in the NetherlandsResearch in context - Hanneke van Laarhoven; Rob Verhoeven; Mark van Berge Henegouwen; Nadia Haj Mohammad; Richard van Hillegersberg; Marije Slingerland; Christina T. Muijs; Bas Wijnhoven; Bianca Mostert; Laurens Beerepoot; Grard Nieuwenhuijzen; Sarah Derks; et al. (EClinicalMedicine)
Summary: Background: Recent studies in patients with resectable adenocarcinoma of the esophagus or gastroesophageal junction (GEJ)—Neo-AEGIS and ESOPEC—have explored the comparison of neoadjuvant chemoradiotherapy (nCRT) with chemotherapy, with conflicting results. To contextualize the findings from these studies using nCRT as a comparator, we aimed to investigate contemporary real-world outcomes of nCRT in patients with adenocarcinoma of the esophagus or GEJ. Methods: From the Netherlands Cancer Registry, patients were selected who were diagnosed between 1 January 2015 and 31 December 2022 with a resectable (cT1N+M0 or cT2-4aNanyM0) esophageal, GEJ or gastric cardia adenocarcinoma and started treatment with nCRT according to the CROSS regimen, that is 5 weekly cycles of carboplatin (AUC 2 mg/mL per minute) and paclitaxel (50 mg/m2) combined with concurrent radiotherapy (41.4 Gy in 23 fractions of 1.8 Gy). Pathologic complete response (pCR) according to Mandard was the primary outcome of this study and defined as complete tumor regression of the primary tumor (Mandard grade I) irrespective of residual nodal involvement. Findings: Of the 4765 included patients, 4170 (87.5%) completed the full CROSS regimen of radiotherapy and chemotherapy. A pCR was observed in 704 (20.5%) of 3439 patients who underwent surgical resection within 16 weeks after completing the CROSS regimen. In the complete study population, the median overall survival (OS) was 33.7 months (95% CI 32.0–35.6), with a 3-year OS rate of 48.1%. Interpretation: Although survival rates in real-world settings are often lower compared to clinical trials, in our real-world cohort the 3-year OS was only 2.6% lower compared to that reported for the group that underwent nCRT in ESOPEC. These real-world results underscore the potential of the CROSS regimen in daily clinical practice. Funding: None.